Special Education Teachers' Perceptions of Students' With Disabilities Ability, Instructional Needs, and Difficulties Using Visual Representations to Solve Mathematics Problems. (May 2019) - van Garderen, Delinda; Scheuermann, Amy; Poch, Apryl L.
In this article, we present findings that examined special education teachers' perception of students' with disabilities ability, instructional needs, and difficulties for using visual representations (VRs) as a strategy to solve mathematics problems. In addition, whether these perceptions differed by instructional grade or setting currently teaching was examined. Survey data from 97 in-service teachers revealed, regardless of instructional setting or grade level taught, that they believe students with disabilities have the ability to learn about and use VRs and need to be taught to use VRs. Furthermore, the special education teachers perceived students with disabilities to have difficulty with all aspects related to using VRs in mathematical problem-solving. Implications for teacher training and development are provided.